2020
DOI: 10.1177/0046958020952911
|View full text |Cite
|
Sign up to set email alerts
|

Team-Based Primary Care Practice Transformation Initiative and Changes in Patient Experience and Recommended Cancer Screening Rates

Abstract: Team-based care has emerged as a promising strategy for primary care practices to provide high-quality care. We examine changes in patient experience of care and recommended cancer screening rates associated with a primary care transformation initiative that established team-based care. Our observational study included 13 academically affiliated primary care practices in the Boston, Massachusetts area that participated in 2 learning collaboratives: the first (2012-2014) aimed to establish team-based primary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
0
14
1
Order By: Relevance
“…Jones et al (2022) evaluated the effect of audit and feedback and patient reminders on screening rates, finding a positive effect for bowel and cervical; however, no effect for breast. Contrary to the previous practice-facilitated and assessment studies, Nguyen et al (2020) found no effect on bowel, breast, and cervical screening rates when assessing the effect of provider education and financial incentives.…”
Section: Qi Projectscontrasting
confidence: 99%
See 1 more Smart Citation
“…Jones et al (2022) evaluated the effect of audit and feedback and patient reminders on screening rates, finding a positive effect for bowel and cervical; however, no effect for breast. Contrary to the previous practice-facilitated and assessment studies, Nguyen et al (2020) found no effect on bowel, breast, and cervical screening rates when assessing the effect of provider education and financial incentives.…”
Section: Qi Projectscontrasting
confidence: 99%
“…Multi-component studies outlined circumstances under which interventions were more likely to optimize the role of PHCWs and increase participation in screening programs through the use of two strategies: engaging whole teams in a practice setting and the use of champions (Tables 2 and 3). The 'whole-of-practice approach' contextual factor is defined as empowering an array of practice staff (eg, administrative staff, nurses, managers, and family physicians) to be involved in cancer screening interventions (Ornstein et al, 2010;Atlas et al, 2011;Shaw et al, 2013;Atlas et al, 2014;Harris et al, 2015;Hills et al, 2015;Mader et al, 2016;Wu et al, 2016;Hountz et al, 2017;Weiner et al, 2017;Bakhai et al, 2018;Nguyen et al, 2020;Hussain et al, 2021;Jones et al, 2022). Ornstein et al (2010) concluded that practices that 'meet as a team to plan evidence-based (quality) improvement strategies : : : can achieve much higher levels of screening than typically reported.'…”
Section: Contextual Factors Of Interventionsmentioning
confidence: 99%
“…After removing duplicates, 19,095 studies underwent title and abstract screening, and then 1541 full‐text studies were assessed for eligibility. In total, 699 studies were included, of which 144 were unique intervention studies included in the current analysis (representing 150 articles) 23–172 …”
Section: Resultsmentioning
confidence: 99%
“…The need for addressing NCDs in India through its primary health care network has been perceived since long. [14][15][16] The comprehensive primary health care (CPHC) component of the Ayushman Bharat initiative of the Government of India aims to achieve the same through the 1.5 lakh health and wellness centers (HWCs) across the country. However, there is a dearth of effective models in primary health care in India for addressing NCDs.…”
Section: Discussionmentioning
confidence: 99%